Coupling Coefficient Parametric For Power Transient Function - Saktioto ' (Komunikasi Fisika Indonesia, 2012)
Fiber coupler are passive devices in which there is no control over phenomena, with a wide range ofparametric changes occurring during fusion due to the fact that the coupled fiber are affected byheating. A simulation of power propagation is developed to describe the effect of power flow tocoupled fibers which continuously propagates from one fiber into the second fiber. In order toexplain these phenomena, characteristics of power speed and power acceleration are examined. Inthis research, power splitting into the second fiber junction that moving along fabrication will bedeveloped by deriving the coupling power depending on times. The model is examined using singlemode fiber with linearly change of refractive index. This simulation results shown the power speedand acceleration are accumulated by time evolution.